Reduced rainfall drives biomass limitation of long‐term fire activity in Australia’s subtropical sclerophyll forests - Michela Mariani; John Tibby; Cameron Barr; Patrick Moss; Jonathan C. Marshall; Glenn B. McGregor (Journal of Biogeography, 2019)
Aim To understand the long‐term drivers of biomass burning in the sclerophyll‐dominated forests of Australia. Location Swallow Lagoon, North Stradbroke Island, Queensland, Australia. Time period Last ca. 8 kyr. Major taxa studied Eucalyptus sensu lato, Leptospermum and Casuarinaceae. Methods High‐resolution pollen and charcoal analyses were undertaken on a ca. 8 kyr sediment record and compared with an independent quantitative precipitation reconstruction inferred from leaf carbon isotopes from the same site. We performed Principal Component Analysis to extract the main vegetation trends around Swallow Lagoon. We then compared vegetation changes to local charcoal records to understand the climate‐vegetation‐fire relationships under different rainfall regimes. The trends in pollen, charcoal and rainfall were analysed using Generalized Additive Models and wavelet coherence. Results Relatively high Casuarinaceae pollen abundance and high charcoal influx were found prior to 3.4 ka, during a phase of high rainfall. Between 3.4 and 1.5 ka there was an increase in Leptospermum ‐type pollen abundance in concert with a decline in both rainfall and charcoal influx. After 1.5 ka low rainfall was generally maintained and a significant increase in Eucalyptus was detected, along with an increase in microscopic charcoal. Main conclusions Our study, from a sclerophyll forest setting that is typical of ~30% of Australia's vegetation, provides a unique example of complex climate‐biomass‐fire feedbacks and highlights biomass limitation of fire activity. High rainfall at Swallow Lagoon is linked to dense Casuarinaceae‐dominated forests and high fire activity prior to 3.4 ka. Between 3.4 and 1.5 ka, a decline in rainfall leads to reduced biomass burning during a phase dominated by shrub communities. After 1.5 ka, a change in fuel type was related to a transition to an open eucalypt forest and greater microscopic charcoal influx.